2017
DOI: 10.1016/j.drugalcdep.2017.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness practice moderates the relationship between craving and substance use in a clinical sample

Abstract: Conclusions:These results indicate that increasing formal mindfulness practice may reduce the link between craving and substance use for MBRP participants and enhance remission resiliency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 58 publications
(44 reference statements)
1
23
0
1
Order By: Relevance
“…Our results regarding mindfulness practice are consistent with theorized mechanisms of how MBRP works. These results also add to existing literature, with some studies supporting both formal and informal mindfulness practice as mechanisms of change (Elwafi et al, 2013;Grow et al, 2015), and another recent study showing that formal practice in particular may reduce the link between craving and substance use (Enkema & Bowen, 2017). Overall, a key focus of MBRP is promoting both on-the-go practice of mindfulness in daily life and sustained formal mindfulness practice.…”
Section: Discussionsupporting
confidence: 68%
“…Our results regarding mindfulness practice are consistent with theorized mechanisms of how MBRP works. These results also add to existing literature, with some studies supporting both formal and informal mindfulness practice as mechanisms of change (Elwafi et al, 2013;Grow et al, 2015), and another recent study showing that formal practice in particular may reduce the link between craving and substance use (Enkema & Bowen, 2017). Overall, a key focus of MBRP is promoting both on-the-go practice of mindfulness in daily life and sustained formal mindfulness practice.…”
Section: Discussionsupporting
confidence: 68%
“…Another study by Grow and colleagues (2015) found greater time spent engaging in home practice was associated with subsequent reductions in substance use and craving at follow-up. Finally, a recent study by Enkema and Bowen (under review) found that following MBRP, formal mindfulness practice moderated the relationship between craving at post-course and number of substance use days at 6-month follow up.…”
Section: Introductionmentioning
confidence: 90%
“…Many empirically supported evidencebased treatments (e.g., motivational interviewing) aimed at reducing alcohol and cannabis use in emerging adults have positive outcomes (Davis et al, 2017;Laporte et al, 2018;Stein et al, 2018). A review of the literature shows that interventions which incorporate aspects of mindfulness, such as mindfulness-based relapse prevention or mindfulness meditation, are effective in reducing alcohol and cannabis use in subclinical (de Dios et al, 2012;Vinci et al, 2014) and clinical populations (Bowen et al, 2014;Enkema & Bowen, 2017;von Hammerstein et al, 2019). I may have observed differing results in this study since this sample consisted of a subclinical emerging adult population.…”
Section: Discussionmentioning
confidence: 99%